Inside Cover: Synthesis of Nω‐Phospho‐l‐arginine by Biocatalytic Phosphorylation of l‐Arginine (ChemCatChem 1/2017). Issue 1 (9th January 2017) - Schoenenberger, Bernhard; Wszolek, Agata; Milesi, Thomas; Brundiek, Henrike; Obkircher, Markus; Wohlgemuth, Roland
Abstract : The Cover picture is an artistic view of the highly selective Nω‐phosphorylation of L‐arginine catalyzed by arginine kinase.In their Full Paper, B. Schoenenberger et al. demonstrate that a highly active and stable arginine kinase, prepared by cloning and expressing the gene for ArgK from Limulus polyphemus in E. coli, ATP‐regeneration using the phosphoenolpyruvate/pyruvate kinase system and reaction monitoring by 31 P‐NMR enable the development of a convenient method for the biocatalytic N ω ‐phosphorylation of L‐arginine. Our results show that tedious multi‐step chemical procedures for the synthesis of N ω ‐phospho‐L‐arginine can be simplified by a straightforward and highly efficient one‐step arginine kinase‐catalyzed phosphorylation of L‐arginine. More information can be found in the Full Paper by B. Schoenenberger et al. onpage 121 in Issue 1, 2017 (DOI:10.1002/cctc.201601080 ).